Observable morphosyntactic, prosodic, and meaning differences among exclamation types support distinct syntactic and semantic structures; the complex taxonomy of exclamations must be incorporated into adequate analyses. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Observable morphosyntactic, prosodic, and meaning differences among exclamation types support distinct syntactic and semantic structures; the complex taxonomy of exclamations must be incorporated into adequate analyses.
iso-id: iso:argument:KzKcrYe0; sha256: sha256:647ce025fed7e31e702ab5b3c43c6a399ed247b03cc8c5178a9a3f87c4e359a2